HOW THE PUNITIVE POWER INFLUENCES IN THE CRIME OF AGGRAVATED ROBBERY FROM A PROSPECTIVE CRIMINOLOGY PERSPECTIVE IN THE LAYKAKOTA NEIGHBORHOOD OF THE CITY OF PUNO IN 2019 - Lady Jesica Ramos Pacompia (2020)
In this article we will develop one of the great problems that the city of Puno suffers in terms of citizen security, “The Crime of theft” in its aggravated modalities. It is essential for the city of Puno to address this problem due to the regularity in which it is presented, even leading in national statistical positions, in terms of crimes according to INEI statistics. For which, our objective is aimed at identifying the area with the highest incidence in terms of the commission of the criminal type of robbery in the city of Puno, being according to our investigations the Laykakota neighborhood. And in this regard we direct our objective to identify the existing prevention form in the population, which will be addressed at different levels: first level (media perspective), second level (precautionary criminology perspective and / or theoretical framework) and a third level (perspective of popular opinion or citizenship). The orientation of this article is to demonstrate that the criminal type of robbery is the most frequent crime and therefore should be considered of primary attention (concern) in the citizens of Puno, also identify the frequency of the commission of the crime of robbery in Puno, attending At the frequency of this crime we intend to identify an alternative way to prevent the crime of theft from the perspective of precautionary criminology.